2018
DOI: 10.1101/307488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudomonas aeruginosaCan Inhibit Growth of Streptococcal Species via Siderophore Production

Abstract: Cystic Fibrosis (CF) is a genetic disease that causes patients to accumulate thick, dehydrated mucus in the lung and develop chronic, polymicrobial infections due to reduced mucociliary clearance. These chronic polymicrobial infections and subsequent decline in lung function are significant factors in the morbidity and mortality of CF. Pseudomonas aeruginosa and Streptococcus spp. are among the most prevalent organisms in the CF lung; the presence of P. aeruginosa correlates with lung function decline and the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
(133 reference statements)
2
7
0
Order By: Relevance
“…We report that co-cultivation with P. aeruginosa results in enhanced growth of S. sanguinis SK36 on either plastic or CF-derived airway cells, while P. aeruginosa growth is relatively unaffected during coculture. These data are consistent with previous reports from our group and others that coculture of streptococci with P. aeruginosa promotes the growth of streptococci, but with no obvious benefit to P. aeruginosa growth (810). Interestingly, in a study examining the interactions between P. aeruginosa and oral streptococci, including S. sanguinis (12, 63), P. aeruginosa growth was inhibited when streptococci were grown as a pioneer colonizer; streptococci can produce hydrogen peroxide (H 2 O 2 ) to react with excess nitrite in the medium to generate reactive nitrogenous intermediates (RNI) for the inhibition of P. aeruginosa growth (12, 13, 63).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We report that co-cultivation with P. aeruginosa results in enhanced growth of S. sanguinis SK36 on either plastic or CF-derived airway cells, while P. aeruginosa growth is relatively unaffected during coculture. These data are consistent with previous reports from our group and others that coculture of streptococci with P. aeruginosa promotes the growth of streptococci, but with no obvious benefit to P. aeruginosa growth (810). Interestingly, in a study examining the interactions between P. aeruginosa and oral streptococci, including S. sanguinis (12, 63), P. aeruginosa growth was inhibited when streptococci were grown as a pioneer colonizer; streptococci can produce hydrogen peroxide (H 2 O 2 ) to react with excess nitrite in the medium to generate reactive nitrogenous intermediates (RNI) for the inhibition of P. aeruginosa growth (12, 13, 63).…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that P. aeruginosa can enhance S. sanguinis SK36 growth either as planktonic or biofilm cells in coculture compared to that of S. sanguinis SK36 monoculture, while the P. aeruginosa population was not significantly impacted by the presence of S. sanguinis (8, 10), a finding confirmed here Fig. S1A.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations